Pemanfaatan Google Sites dalam Pembuatan Majalah Digital oleh Siswa MAN 3 Solok - Atikah Gusriani; Lisa Yuliarti; Ranti Karmila; Natasya Lady Munaroh; Angel Novita Ramadani; Grisma Yuliarta; Rizka Frasa Kutia (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
This article examines the implementation of Google Sites as a platform for developing a digital magazine by students of MAN 3 Solok. The research aims to describe the design, execution, and evaluation processes of utilizing Google Sites in creating a digital magazine, as well as to identify the challenges and benefits encountered. The method employed involved training and direct mentoring for 20 members of the student council at MAN 3 Solok. The results indicate that 70% of participants successfully accessed the website and created the digital magazine effectively, while 30% faced operational and infrastructure-related technical challenges. The use of Google Sites has proven effective in enhancing digital literacy, creativity, and collaboration among students in creating digital-based school publications. Through this activity, students not only gained technical skills but also developed essential creative thinking, problem-solving, and collaborative abilities in the digital era.